NEW OPPORTUNITIES IN TREATMENT OF SEVERE SYSTEMIC TYPE OF JUVENILE ARTHRITIS - R.V. Denisova; E.I. Alexeeva; A.O. Lisitsin; S.I. Valieva; T.M. Bzarova (Вопросы современной педиатрии, 2010)
The article presents a case report of a severe clinical course of systemic type of juvenile arthritis, resistant to treatment with corticosteroids and classic immunosuppressive agents in girl 9 years old. Biological agent — tocilizumab showed beneficial effect: exudative lesions of joints, morning joint stiffness stopped and the range of motions restored in almost all affected joints in 8 weeks of treatment. A girl became more active, her emotional state improved. Laboratory signs of disease’s activity (ESR, concentration of C-reactive protein in plasma) were normalized in 4 weeks. The drug induced development of clinical and laboratory remission of a disease. Key words: children, juvenile arthritis, treatment, tocilizumab. (Voprosy sovremennoi pediatrii — Current Pediatrics. – 2010;9(4):160-167)